Information and Communication Technologies and the Law: Some Concrete Boundaries - Ayuda, Fernando Galindo (Frontiers in Law, 2023)
Laws and regulations are crucial in governing technology, especially in regards to its development and use in society. While it is undeniable that technology, specifically information and communication technologies (ICTs), has a relationship with the law, this relationship should be restricted to the actions of judges and lawyers rather than being exercised directly or indirectly by ICTs themselves. There are various proposals that contradict this idea and pose a threat to the rule of law. This article aims to address this issue and provide concrete examples and references to illustrate the importance of avoiding such attitudes.